Dietary patterns of adults with asthma treated at a referral center for asthma - Carra Forte, Cristina; Carra Forte, Gabriele; Torres Hennemann, Maria Luiza; Tweedie Preto, Luiza; Carnevale Almeida, Jussara; de Tarso Roth Dalcin, Paulo; Canuto, Raquel (Clinical and Biomedical Research, 2021)
Objectives: To assess the association between dietary patterns, nutritional status and asthma control in patients treated at a referral center for asthma in Porto Alegre, Brazil. Methods: This is a cross-sectional study with 198 adult asthma patients. Participants answered 24h food recall and questionnaire of the history of the disease, degree of control and severity, in addition to performing pulmonary and anthropometric assessments. We used exploratory factor analysis and extraction of the factors the method of analysis of main components to derive the dietary patterns. Results: The mean of body mass index was 29.6 ± 5.7 kg/m²; and 41.9% were classified as obese. Regarding the severity of the disease, 72.7% were classified as having severe persistent asthma. The degree of control, 59.6% of patients had uncontrolled asthma. Three dietary patterns were identified: "Sugars", "Healthy", "Fats and Alcohol." It was observed in this study, that the Fat and Alcohol pattern was significantly associated with male gender. However, no associations were observed between the other variables and dietary patterns. Conclusion: This study was the first to identify the dietary patterns in asthmatics in Brazil. Patterns found in the present study were “Sugars”, “Healthy” and “Fats and Alcohol”. However, not a significant association between the three standards and nutritional status and disease control.